2017
DOI: 10.1039/c7py01233k
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial synthesis of soluble conjugated polymeric nanoparticles and tunable multicolour fluorescence sensing

Abstract: Combinatorial polymerization method has been exploited to prepare a library of soluble conjugated polymeric nanoparticles (SCPNs), by varying symmetrical monomers, Ax and By (x > 2, y ≥ 2), plus modification with variant terminal groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…It is evident that electron-rich organic analytes (alkylamine and arenes) cluster together, while analytes with electron deficient substituents (nitroaromatics, aromatic aldehydes, and aliphatic acids) form separate groups. Alkyl alcohols, causing little fluorescence change, cluster together with control group, and inorganic strong acids, which tend to a Note that "SCPN (xyz) " means the SCPN is prepared from the polycondensation between monomer A (x) and B (y) in confined nanoreactors 44 and post-modified with terminal group T (z) (which is not afforded for sensors in A−D columns). robustly quench the fluorescence of SCPN sensors form another cluster.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is evident that electron-rich organic analytes (alkylamine and arenes) cluster together, while analytes with electron deficient substituents (nitroaromatics, aromatic aldehydes, and aliphatic acids) form separate groups. Alkyl alcohols, causing little fluorescence change, cluster together with control group, and inorganic strong acids, which tend to a Note that "SCPN (xyz) " means the SCPN is prepared from the polycondensation between monomer A (x) and B (y) in confined nanoreactors 44 and post-modified with terminal group T (z) (which is not afforded for sensors in A−D columns). robustly quench the fluorescence of SCPN sensors form another cluster.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…42,43 A large number of SCPNs were facilely prepared with combinatorial chemistry method, and tunable fluorescence emissions were achieved by simply varying the monomers and terminals. 44 Herein, we report an array consisting of 36 sets of SCPNs and the vector of every analyte in the full 108dimensional space was used for the identification of volatile compounds, including nitroaromatics, aromatic aldehydes, arenes, alkyl alcohols, amines, and acids (30 kinds of analytes). PCA and HCA indicated that the diversities of electronic structures, miscibility and saturated vapor pressure of analytes were keys in differentiating these analytes.…”
mentioning
confidence: 99%
“…Conjugated microporous polymers (CMPs) have found increasing interest as potential materials for gas storage and separation . The combined chemical and thermal stability of conjugated polymers (CPs) allow to potentially consider these organic materials to be complementary to their inorganic counterparts such as zeolites, ceramic, and carbon molecular sieves .…”
Section: Introductionmentioning
confidence: 99%
“…The combined chemical and thermal stability of conjugated polymers (CPs) allow to potentially consider these organic materials to be complementary to their inorganic counterparts such as zeolites, ceramic, and carbon molecular sieves . To obtain a microporous structure, CPs are either crosslinked to form a network of covalently interconnected chains, or a (hyper)branched structure is formed to disrupt the π‐stacking of polymer backbones . The former procedure “crosslinking” however often results in insoluble polymer network difficult to process in membranes, and therefore the branching technique is more appealing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation